ANALISIS KELAYAKAN USAHA ANYAMAN LIDI DI KABUPATEN MIMIKA (STUDI KASUS PADA USAHA KERAJINAN TANGAN MASYARAKAT NAWARIPI) - Frengki Nainggolan; Habel Taime (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2017)
The aim this study was to find out the feasibility of wicker business in mimika regency.The analytical tool used is one sample t-test in order to test whether a particular value (parameter given as comparison) is significantly differentor not with a sample average.The result of the research showed that the wicker business in Mimika regency is feasible to be implemented. One sample t-test shows the t-value (-102.797) <t table (2.093) so Ho is accepted that means no significant difference between the actual value of the non-financial aspect and the ideal value of the nonfinancial aspect, which means the effort Concerned is non-financially feasible